(untitled) (Research, Society and Development, 2021)
Objective: to analyze scientific productions in order to understand and discuss how the educational use of audiovisual resources in teaching mental health in nursing education is being investigated by researchers. Methodology: literature review carried out in the databases of the Virtual Health Library, in 2021. Four categories were defined for analysis: research methodology; theoretical fundamentals of research; objectives of the use of audiovisuals and the perspective of teachers in the use of audiovisuals. Results: 20 articles, published between 2003 and 2020, national and international. There is a predominance of studies of effectiveness and description of experiences. Audiovisuals are used in order to increase knowledge, understanding and critical reflection and the teachers perceive them as an instrument of the teaching-learning process that facilitate reflection. The Active Learning methodology is the main theoretical framework used by the authors of the studies. Final considerations: it is evident the importance of expanding theoretical and empirical research that collaborate to understand the process of producing meanings actively by students, when they have contact with an audiovisual text.